Parental Knowledge Influenced The Effectiveness of Role Play on Food Safety Behavior in School-Age Children - Kusumawardani, Lita Heni; Kartikasari, Aprilia; Pratama, Koernia Nanda (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Health problems due to unsafe food in Indonesia often occur, especially amongst school-aged children. School-aged children need to be given health education related to food safety to prevent food poisoning. Parents have an essential role in health among school-aged children. Objectives: This study aimed to determine the most influential factors of role-play on food safety behavior among school-aged children (6–12 years). Method: The study design was quasi-experimental with pre-and post-test designs. It involved 101 school-age children equally divided into intervention and control groups. Multistage random sampling was used to determine the research area and school where the research was conducted, while the research subject was selected using a simple random sample. The intervention group was treated in the form of a group process with the implementation of a role play for four weeks, which was carried out four times a month and lasted for 40 minutes per session. The analysis of data was performed using the ANOVA test. Results: The results showed that parental knowledge had a significant effect on the influence of therapeutic role-play on students’ learning (p = 0.004), attitudes (p = 0.007), and prevention skills (p = 0.009). Parental knowledge is the most influential factor in effective therapeutic role-play on food safety behaviors among school-aged children (6–12 years). Conclusion: The role-play method can improve the food safety behavior of school-aged children. The role-play method should be an effective and interactive health education intervention for elementary school-aged children. Role-play can involve the food safety behavior of parents and teachers in further study.